A multifunctional metal–organic framework with a μ3-OH− site for gas and vapor sorption and selective detection of nitrofurantoin. Issue 3 (22nd December 2021) - Zhang, Yujuan; Gao, Lingling; Ma, Sai; Hu, Tuoping
Abstract : The excellent sorption capacity of 1 for CO2 /H2 O vapor is due to the weak interactions between μ 3 -OH − in 1 and CO2 /H2 O. The fluorescence sensing of 1 for NFT is ascribed to the combined effect of competitive absorption, weak interactions and PET. Abstract : A porous 3D multifunctional Zn-MOF (1 ), namely {[Zn2.5 (DDPP)(OH)(H2 O)]·H2 O·1.5DMF} n (H4 DDPP = 3, 5-di(2′, 5′-dicarboxylphenyl)pyridine, DMF = N, N -dimethylformamide), was solvothermally synthesized by the reaction of a H4 DDPP ligand and zinc salts. 1 exhibits a high adsorption performance for N2 (246.2 cm 3 g −1 at 77 K) and CO2 (116.1 cm 3 g −1 at 273 K) as well as excellent selective separation for CO2 /CH4 (V : V = 0.5 : 05) and CO2 /CH4 (V : V = 0.05 : 0.95) with selectivity coefficients of 79.3 and 25.4 at 298 K and 1 bar, respectively. Meanwhile, 1 shows a great performance for H2 O vapor sorption and the uptake amount of H2 O vapor is 281.9 cm 3 g −1 (at 298 K and P / P 0 = 0.99), which is comparable to that reported in the literature. Furthermore, 1 has an excellent separation ability for H2 O vapor in H2 O/CH3 OH mixed vapor and the selectivity of 1 for H2 O/CH3 OH (V : V = 0.1 : 0.9) and H2 O/CH3 OH (V : V = 0.05 : 0.95) is 254.6 and 94.9 at 298 K and 1 bar, respectively. More importantly, the Grand Canonical Monte Carlo (GCMC) simulation shows that the reason for the good adsorption capacity of 1 for CO2 and H2 O vapor is attributed to the pore structure of 1 and the interaction between the coordinated H2 O molecules and μ3 -OH − in 1 and CO2 or H2 O molecule. In addition, 1 shows sensitive sensing ability for nitrofurantoin (NFT) and the detection limit (DL) was 5.3 × 10 −8 M. Moreover, the fluorescence sensing mechanism of 1 for NFT can mainly be attributed to the competitive absorption between the absorption spectrum of NFT and the emission spectrum of 1, the weak interactions between μ3 -OH − in 1 and NFT and photoinduced electron transfer from 1 to NFT.